Bimetallic oxides and preparation methods thereof and application of signal reversal detection of antibiotics
By using bimetal oxide Sc2O3@CuO and nano-gold particles (AuNPs), the photocurrent direction flip sensor is constructed, and combined with enzyme-clearing signal amplification technology, the problem of false positive and false negative errors in the detection of antibiotics in the existing technology is solved, and the problem of false positive and false negative errors is achieved. High selectivity and sensitivity detection effects.
Patent Information
- Application Number
- CN202310795134.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-06-30
AI Technical Summary
Existing photoelectrochemical sensors have false positive or false negative errors when detecting antibiotics, and the one-way signal response strategy is difficult to eliminate background signal interference, affecting the selectivity and sensitivity of detection.
Bimetal oxide Sc2O3@CuO is used as the photoelectric active material, and combined with the LSPR effect of nano-gold particles (AuNPs), a photocurrent direction flip sensor is constructed, and signal output is enhanced through enzyme-cut signal amplification technology to improve detection selectivity and sensitivity.
High selectivity and high sensitivity detection of trace antibiotics in food is achieved, eliminating background signal interference and improving detection accuracy and stability.
Smart Images

Figure CN116789163B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biotechnology, and in particular to a bimetallic oxide, a preparation method thereof, and application of signal flipping detection of antibiotics. Background Art
[0002] Antibiotic residues in food are a major hidden danger that affects the safety of animal-derived foods. Among them, kanamycin (Kana), as a second-line antibiotic, is widely used as a drug for both humans and animals because of its low price and broad antibacterial spectrum. However, irrational use can also lead to its residues in animal-derived foods and the environment. Kana remaining in food and the environment can enter the human body through the food chain and the biological circulation system, causing varying degrees of damage to human health, such as ototoxicity, nephrotoxicity and antibiotic resistance. Therefore, in order to ensure food safety, it is necessary to develop a simple, rapid and highly sensitive method for detecting residues of antibiotics such as Kana in food.
[0003] Photoelectrochemical sensors have attracted much attention in the detection of antibiotics due to their low cost, high sensitivity, low background signal, short response time, ease of use and miniaturization. However, most of the reported sensors are built based on a unidirectional signal response strategy, which is not conducive to eliminating the adverse effects of interferents in actual samples on the detection anti-interference ability and sensitivity. False positive or false negative errors may occur, which seriously limits their application and development in antibiotic analysis and detection.
[0004] Photocurrent direction reversal sensors have the advantages of high selectivity and high sensitivity and have become popular recently. As the core element of the photocurrent direction reversal system, the photoelectrically active material directly affects its reversal efficiency. Most of the existing reversal materials are single semiconductors, which reduces the photoelectric conversion efficiency. Therefore, developing a high-performance new bimetallic oxide reversal material and applying it to the antibiotic photocurrent direction reversal detection platform is a meaningful research work worthy of in-depth exploration. Summary of the invention
[0005] In view of this, the main purpose of the present invention is to provide a bimetallic oxide of a photoelectrochemical biosensor suitable for detecting trace antibiotics in food, and a preparation method and application thereof; the biosensor is mainly prepared by constructing a photocurrent direction reversal strategy to eliminate the interference of background signals, and at the same time using enzyme cleavage signal amplification technology to increase signal output, thereby achieving the purpose of improving the selectivity and sensitivity of detecting antibiotics such as Kana.
[0006] The technical solution provided by the present invention is as follows:
[0007] A bimetallic oxide is scandium trioxide@copper oxide, and has an octahedral crystal structure composed of Sc2O3 and CuO, which is abbreviated as Sc2O3@CuO in this article.
[0008] The X-ray powder diffraction pattern of the above-mentioned bimetallic oxide has characteristic peaks at the following 2θ values: 22.0°±0.20°, 31.5°±0.20°, 36.4°±0.20°, 43.0°±0.20°, 52.4°±0.20°, 62.5°±0.20°, 32.7°±0.20°, 35.5°±0.20°, 38.8°±0.20°, 48.7°±0.20°, 53.5°±0.20°, 58.4°±0.20° and 61.6°±0.20°.
[0009] A preparation method of a bimetallic oxide comprises: heating a metal organic framework MOF-919-Sc crystal at 350-650° C. to react and obtain a black powder, thereby obtaining Sc2O3@CuO.
[0010] The preparation method of MOF-919-Sc crystals includes: firstly dissolving scandium chloride hexahydrate, copper nitrate trihydrate and 4-pyrazole carboxylic acid in DMF, and heating at 80-120° C. to synthesize MOF-919-Sc crystals. The MOF-919-Sc crystals become green powder after drying.
[0011] A bimetallic oxide composite material, mainly composed of the above-mentioned Sc2O3@CuO and nano-gold particles (AuNPs) electrostatically adsorbed on the surface of the Sc2O3@CuO octahedron. Herein, the bimetallic oxide composite material is abbreviated as "Sc2O3@CuO@AuNPs". Preferably, the particle size of AuNPs is 10 to 15 nm.
[0012] The preparation method of the Sc2O3@CuO@AuNPs comprises: firstly subjecting the Sc2O3@CuO and AuNPs to ultrasonic dispersion treatment in water, and then filtering and drying the Sc2O3@CuO and AuNPs.
[0013] The preparation method of AuNPs comprises: firstly heating a tetrachloroauric acid solution to boiling under stirring conditions, then rapidly adding a sodium citrate solution under vigorous stirring, condensing and refluxing while continuing to stir, and then taking out and cooling with ice water to room temperature.
[0014] A photocurrent signal reversal type photoelectrochemical sensor, comprising: a TiO2 / ITO electrode and a hairpin probe HP2 (Hairpin probe 2) marked with amino groups, an auxiliary probe S2 marked with biotin and a signal probe modified on the surface of the TiO2 / ITO electrode, wherein the signal probe is Sc2O3@CuO@AuNPs coated with streptavidin (SA);
[0015] The auxiliary probe S2 is mainly obtained by the enzymatic cleavage reaction between the auxiliary probe S1 released by competition and the hairpin probe HP1 (Hairpin probe 1) labeled with biotin under the action of an enzyme, wherein the auxiliary probe S1 released by competition is mainly obtained by mixed incubation of MNPs-Apt / S1 and the antibiotic to be tested, wherein "MNPs-Apt / S1" is the abbreviation of "magnetic nanoparticle-aptamer / auxiliary probe S1";
[0016] The auxiliary probe S2 opens the hairpin probe HP2, exposing the biotin on the auxiliary probe S2 on the surface of the TiO2 / ITO electrode. The biotin binds to streptavidin SA, so that the signal probe is modified to the surface of the TiO2 / ITO electrode to form a Sc2O3@CuO@AuNPs / TiO2 / ITO electrode whose photoelectric signal is opposite to that of the TiO2 / ITO electrode.
[0017] A method for preparing the above-mentioned photoelectrochemical sensor comprises the steps of:
[0018] Adding a cross-linking agent: first adding a chitosan (CS) solution to the surface of the TiO2 / ITO electrode, then dropping a glutaraldehyde (GLD) solution and incubating at room temperature, sequentially modifying the TiO2 / ITO electrode with CS and GLD to obtain a CS / TiO2 / ITO electrode; wherein the TiO2 / ITO electrode can generate an initial anode photocurrent signal;
[0019] Adding hairpin probe HP2: first assembling the hairpin probe HP2 onto the CS / TiO2 / ITO electrode by incubation at room temperature, and then blocking the active sites on TiO2 with bovine serum (BSA) to prepare a BSA / HP2 / CS / TiO2 / ITO electrode;
[0020] Adding auxiliary probe S2: first react and combine carboxyl magnetic beads (MNPs) with aptamer Apt to obtain MNPs-Apt; then hybridize MNPs-Apt with auxiliary probe S1 to form MNPs-Apt / S1, and obtain MNPs-Apt / S1 resuspension; add the antibiotic to be tested to the MNPs-Apt / S1 resuspension to react, release the auxiliary probe S1 in the MNPs-Apt / S1, magnetically separate, and take the supernatant containing the auxiliary probe S1; add the hairpin probe HP1 labeled with biotin and ExoⅢ enzyme to the supernatant containing the auxiliary probe S1 for enzyme cleavage reaction to form the auxiliary probe S2 labeled with biotin; assemble the auxiliary probe S2 onto the BSA / HP2 / CS / TiO2 / ITO electrode to obtain the S2 / BSA / HP2 / CS / TiO2 / ITO electrode;
[0021] Adding a signal probe: first dissolve the above-mentioned Sc2O3@CuO@AuNPs in SA solution to react, synthesize Sc2O3@CuO@AuNPs-SA, and prepare a Sc2O3@CuO@AuNPs-SA suspension; add the Sc2O3@CuO@AuNPs-SA suspension to the surface of the S2 / BSA / HP2 / CS / TiO2 / ITO electrode for incubation to obtain a Sc2O3@CuO@AuNPs-SA / S2 / BSA / HP2 / CS / TiO2 / ITO electrode.
[0022] The antibiotic is Kana, tetracycline, oxytetracycline or penicillin. Apt herein is an existing aptamer corresponding to a specific antibiotic.
[0023] The preparation method of the TiO2 / ITO electrode includes: firstly synthesizing NH2-MIL-125(Ti) by a solvothermal method, and carbonizing the NH2-MIL-125(Ti) to obtain a light yellow solid powder TiO2 polyhedron; then preparing a TiO2 polyhedron suspension using the TiO2 polyhedron as a solute; and then dripping the TiO2 polyhedron suspension onto an ITO electrode to obtain the TiO2 / ITO electrode. The step of carbonizing the NH2-MIL-125(Ti) includes heating the NH2-MIL-125(Ti) to 300-450°C for a heating reaction to obtain a light yellow solid.
[0024] An application of the above-mentioned photocurrent signal reversal type photoelectric chemical sensor in detecting the concentration of antibiotics in food.
[0025] Based on the above application, the method comprises the following steps: placing the current direction reversal type photoelectrochemical sensor in a Tril-HCl buffer solution containing 0.1M ascorbic acid at pH 7.4 for PEC detection, detecting the photocurrent signal of the antibiotic at different concentrations; and constructing a linear equation between the antibiotic concentration and the photocurrent signal based on the detection result. Preferably, the detection voltage is 0V.
[0026] In the step of adding the auxiliary probe S2, the antibiotic solution to be tested is added to the MNPs-Apt / S1 resuspension, mixed evenly and placed on a constant temperature oscillator at 37°C for 30 to 120 minutes, the auxiliary probe S1 in the MNPs-Apt / S1 is released through competition, and then the supernatant is obtained by magnetic separation, and the supernatant contains the released auxiliary probe S1. Preferably, when the antibiotic to be tested is Kana, the oscillation incubation time between it and the MNPs-Apt / S1 is 90 minutes.
[0027] In the step of adding the signal probe, the Sc2O3@CuO@AuNPs-SA suspension is added to the surface of the S2 / BSA / HP2 / CS / TiO2 / ITO electrode and incubated at 37°C for 40 to 160 minutes to obtain the Sc2O3@CuO@AuNPs-SA / S2 / BSA / HP2 / CS / TiO2 / ITO electrode. Preferably, the binding time of Sc2O3@CuO@AuNPs-SA and the S2 / BSA / HP2 / CS / TiO2 / ITO electrode is 120 minutes.
[0028] Based on the above application, when the concentration range of antibiotic Kana is 0.1-500 pmol / L, the constructed linear regression equation is y=-0.621x-1.502, where x is lgC Kana , R 2 =0.997, the detection limit is 0.09 pmol / L; wherein y is the photocurrent signal detected by the sensor, in μA; C Kana Represents the concentration of Kana.
[0029] Therefore, the bimetallic oxide Sc2O3@CuO provided by the present invention is an octahedral crystal structure material composed of Sc2O3 and CuO, and the specific surface area of the material is 55.28 m 2 / g, and the average pore size is 13.6nm. The larger pore size and high specific surface area are conducive to the adsorption of light and give the Sc2O3@CuO material good photoelectric properties.
[0030] The bimetallic oxide composite material Sc2O3@CuO@AuNPs provided by the present invention is composed of Sc2O3@CuO and AuNPs adsorbed on the surface of Sc2O3@CuO by electrostatic adsorption, and has an absorption peak in the visible light region and excellent photoelectric properties. In addition, after the composite material is modified on the surface of the TiO2 / ITO electrode, a photocurrent signal in the opposite direction to the photocurrent of the TiO2 / ITO electrode can be generated.
[0031] The Sc2O3@CuO octahedron in the above-mentioned current direction reversal photoelectrochemical sensor provided by the present invention has excellent photoelectric activity, and at the same time, the LSPR effect of AuNPs is combined to form materials such as Sc2O3@CuO@AuNPs, which improves the response value of the PEC signal source; the photocurrent direction reversal strategy is introduced into the detection application of antibiotics to eliminate background signal interference, and has excellent anti-interference ability and high sensitivity; the Exo III auxiliary signal cycle amplification technology in the homogeneous phase is used to increase the solid-liquid contact area, which is conducive to improving the capture efficiency of the target object, and at the same time, the signal conversion and signal cycle amplification of the target object Kana are realized. Therefore, the sensor provided by the present invention is based on the TiO2 nanomaterial derived from MOFs, combined with the photocurrent direction reversal strategy and enzyme cleavage signal amplification technology, and can establish a new PEC method for detecting antibiotics. The method has the advantages of high sensitivity, good accuracy, strong selectivity, high stability, good reproducibility, etc., and realizes the rapid detection of antibiotics in animal-derived foods such as milk and honey, which has potential value in ensuring food safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 These are SEM images of MOF-919-Sc (left picture) and Sc2O3@CuO (right picture) materials provided in Example 1 of the present invention.
[0033] Figure 2 It is the XRD diagram of MOF-919-Sc(A) and Sc2O3@CuO(B) materials provided in Example 1 of the present invention.
[0034] Figure 3 This is the XPS spectrum of the Sc2O3@CuO polyhedron provided in Example 1 of the present invention, wherein Figure A is the full spectrum, Figure B is the O1s map, Figure C is the Cu 2p map, and Figure D is the Sc 2p map.
[0035] Figure 4 This is a N2 adsorption-desorption curve diagram of the Sc2O3@CuO polyhedron provided in Example 1 of the present invention.
[0036] Figure 5 This is a characterization diagram of the Sc2O3@CuO@AuNPs polyhedron provided in Example 2 of the present invention, wherein Figure A is a HRTEM diagram and Figure B is an EDS element mapping diagram.
[0037] Figure 6 It is the UV-vis-NIR spectrum diagram of AuNPs and Sc2O3@CuO@AuNPs provided in Example 2 of the present invention.
[0038] Figure 7 It is a structural characterization diagram of TiO2 used in Example 3 of the present invention; wherein, Figure A is the XRD spectrum of TiO2, and Figure B is the TEM diagram (a), EDS element mapping diagram (b), (c) and (d) of TiO2.
[0039] Figure 8 This is the XPS spectrum of the TiO2 polyhedron used in Example 3 of the present invention, wherein Figure A is the full spectrum, Figure B is the Ti2p map, and Figure C is the O1s map.
[0040] Fig. 9 It is a nitrogen adsorption-desorption curve diagram of TiO2 used in Example 3 of the present invention.
[0041] Fig.10 It is the UV-vis-NIR spectrum of TiO2 used in Example 3 of the present invention.
[0042] Fig.11 This is the photocurrent signal response of various modified electrodes provided in Example 3 of the present invention.
[0043] Fig.12 This is a possible photogenerated electron transfer mechanism diagram between TiO2 and TiO2 / / Sc2O3@CuO@AuNPs provided in Example 3 of the present invention, wherein the left figure is a photogenerated electron transfer mechanism diagram of TiO2; the right figure is a photogenerated electron transfer mechanism diagram between TiO2 / / Sc2O3@CuO@AuNPs.
[0044] Fig.13 This is a schematic diagram of the principle of detecting Kana based on the photocurrent direction reversal strategy and enzyme cleavage signal amplification technology provided in Example 4 of the present invention.
[0045] Fig.14 This is a photocurrent response diagram during the assembly process of the photocurrent sensor provided in the fourth embodiment of the present invention.
[0046] Fig.15 This is an electrochemical impedance response diagram of the photocurrent sensor assembly process provided in Example 4 of the present invention.
[0047] Fig.16 This is a polyacrylamide gel electrophoresis diagram for verifying a multi-step DNA binding reaction during the assembly process of the photocurrent sensor provided in the fourth embodiment of the present invention.
[0048] Fig.17This is a diagram showing the influence of Kana reaction time on photocurrent response during the construction of the photocurrent sensor provided in the fourth embodiment of the present invention.
[0049] Fig.18 This is a diagram showing the influence of the signal probe binding time on the photocurrent response during the construction of the photocurrent sensor provided in the fourth embodiment of the present invention.
[0050] Fig.19 The photocurrent response diagram (A) and the constructed standard curve diagram (B) of detecting different concentrations of Kana using the photocurrent sensor provided in Example 4 of the present invention.
[0051] Fig. 20 This is a diagram of the selective experimental results of detecting Kana by the photocurrent sensor provided in the fourth embodiment of the present invention.
[0052] Fig.21 This is a diagram showing the stability test results of detecting Kana of the photocurrent sensor provided in the fourth embodiment of the present invention.
[0053] Fig. 22 This is a graph showing the reproducibility of the experimental results of detecting Kana using the photocurrent sensor provided in the fourth embodiment of the present invention. DETAILED DESCRIPTION
[0054] The technical solution of the present invention is further described in detail below through specific implementation methods.
[0055] The present invention introduces a signal flipping strategy and an enzyme cleavage signal amplification technology to improve the sensitivity and selectivity of detecting antibiotics. First, a TiO2 polyhedron derived from MOFs (NH2-MIL-125) is fixed on the surface of an ITO electrode to generate an initial anode photocurrent signal; then HP1 is fixed on the surface of the TiO2 polyhedron, and the remaining active sites are blocked. Combined with magnetic separation technology, antibiotics or target-induced ExoⅢ enzyme cleavage signal amplification technology is applied to generate a large amount of biotin-labeled auxiliary probes S2; the auxiliary probe S2 opens HP2 to form double-stranded DNA through base complementary pairing, and based on the specific binding of biotin and streptavidin, the Sc2O3@CuO@AuNPs polyhedron derived from MOF-919-Sc is introduced into the modified electrode surface to generate a cathode detection signal in the opposite direction to the background signal; when only the corresponding antibiotic is present, the photocurrent signal will flip from the anode to the cathode, and the degree of signal enhancement is positively correlated with the amount of the corresponding antibiotic.
[0056] The following further describes the technical solution provided by the present invention by taking the sample containing the antibiotic Kana as the detection object.
[0057] All aqueous solutions used in the present invention were prepared using ultrapure water from a Milli-Q filtration system (Millipore Corp., USA). The reagents and materials used were substantially all analytical grade. The nucleic acids used were purchased from Sangon Biotech (Shanghai) Co., Ltd., and the nucleic acid sequences are shown in Table 1.
[0058] Reagents and materials used in the embodiments of the present invention : 300 nm carboxyl magnetic nanoparticles (MNPs) were from Baiyun Nanotechnology Co., Ltd.; sodium hydroxide and potassium chloride were from Tianjin Tianli Chemical Reagent Co., Ltd.; anhydrous ethanol and citric acid were from Tianjin Kaitong Chemical Reagent Co., Ltd.; tris(hydroxymethyl)aminomethane was from Beijing Solebold Technology Co., Ltd.; hydrochloric acid was from Luoyang Haohua Chemical Reagent Co., Ltd.; magnesium chloride and N,N′-dimethylformamide (DMF) were from Shanghai MacLean Biochemical Technology Co., Ltd.; sodium chloride, glutaraldehyde, and titanium isopropoxide were from Tianjin Komio Chemical Reagent Co., Ltd.; glacial acetic acid (≥99.5%) was from Tianjin Fuchen Chemical Reagent Factory; chitosan (CS), terephthalic acid, methylene blue, scandium trichloride, N-(3-dimethylaminopropyl)-N-ethyl-carbonyl Imine hydrochloride (≥99.0%), copper nitrate trihydrate, 4-pyrazolecarboxylic acid, and kanamycin analytical standards (≥99.0%) were from Hai Aladdin Biochemical Technology Co., Ltd.; bovine serum albumin (BSA) and tetrachloroauric acid (≥99.0%) were from Sigma-Aldrich (Shanghai) Trading Co., Ltd.; anhydrous methanol was from Haotian Reagent Chemical Co., Ltd.; ascorbic acid, potassium ferrocyanide, and potassium ferrocyanide were from Sinopharm Chemical Reagent Co., Ltd.; tetraisopropyl titanate (≥98.0%) and aminoterephthalic acid were from Beijing Bailingwei Technology Co., Ltd.; N-hydroxysuccinimide was from Beijing Kangwei Century Biotechnology Co., Ltd.; PBS buffer, erythromycin, doxycycline hydrochloride, tetracycline, enrofloxacin, streptomycin, 500bp Marker, red fluorescent nucleic acid dye, and PAGE kit were from Beijing Solebow Technology Co., Ltd.; exonuclease III (5000 units) was from New England Biotechnology, USA; streptavidin (SA) was from Shanghai Shenggong Bioengineering Technology Service Co., Ltd.; ELISA kit was from Shanghai Baiyi Biotechnology Co., Ltd.; ITO electrode was from Zhuhai Kaiwei Optoelectronics Technology Co., Ltd.; saturated calomel electrode and platinum electrode were from Shanghai Yidian Scientific Instrument Co., Ltd.
[0059] Table 1 Nucleic acid names and base sequences
[0060]
[0061] The experimental instruments used in the embodiments of the present invention are as follows: :
[0062] UV-visible spectrophotometer (DS5, Edinburgh, UK), transmission electron microscope (JEOL, JEM-2100F, Japan), X-ray diffractometer (Bruker D8 Advance, Germany), multifunctional imaging electron spectrometer (ThermoESCALAB 250XI, USA), pH meter (pH213, HANNA, Italy), digital electronic constant temperature water bath (HH-2, Jintan Danrui Electric Appliance Factory), electric constant temperature incubator (DHG-9146A, Shanghai Jinghong Experimental Equipment Co., Ltd.), vortex mixer (XH-C, Jintan Guowang Experimental Instrument Factory), high-speed centrifuge (Eppendorf, Centrifuge5424R), steam boiler for high pressure sterilization (HVE-50, HIRAYAMA, Japan), electrophoresis apparatus (DYCZ25D, Beijing Liuyi Biotechnology Co., Ltd.), electrophoresis apparatus power supply (DYY-7C, Beijing Liuyi Instrument Factory), stainless steel high pressure reactor (Shanghai Hujia Instrument Equipment Co., Ltd. Company), precision electronic balance (FA1204, Qingdao Jinke Instrument Co., Ltd.), magnetic separation plate (Baiyun Nano Technology Co., Ltd.), adjustable series micropipette (Eppendorf, Germany), ordinary low-temperature refrigerator (Qingdao Haier Group Co., Ltd.), CNC ultrasonic cleaner (KQ-300DE, Kunshan Ultrasonic Instrument Co., Ltd.), centrifuge (Hunan Xiangyi Company), electric constant temperature blast drying oven (Shanghai Jinghong Experimental Equipment Co., Ltd.), stainless steel high-pressure reactor (Shanghai Hujia Instrument Equipment Co., Ltd.), collector constant temperature heating magnetic stirrer (DF-101S, Gongyi Yuhua Instrument Co., Ltd.), CHI660E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.).
[0063] The solution configured in the embodiment of the present invention is as follows:
[0064] (1) 0.1 mmol / L Tris-HCl (pH = 7.4): Weigh 12.114 g of tris(hydroxymethyl)aminomethane (Tris), dissolve it in 900 mL of Milli-Q water, adjust the pH to 7.4 with 0.1 mmol / L hydrochloric acid (HCl), and make up to 1000 mL.
[0065] (2) Hybridization buffer (pH = 7.4): Weigh 2.4228 g Tris, 5.8440 g sodium chloride, and 2.0330 g magnesium chloride hexahydrate, dissolve in 950 mL Milli-Q water, adjust the pH to 7.4 with 0.1 mol / L HCl, make up to 1000 mL, and sterilize by high pressure before use.
[0066] Photocurrent experimental method
[0067] pass PhotocurrentExperimental verification of the step-by-step assembly process on the electrode surface. Photocurrent The experiment was conducted on an electrochemical workstation CHI660E. A xenon lamp (PLS-SXE300) equipped with a 420nm cutoff filter was used as a light source (λ>420nm), an ITO electrode (diameter, φ5.6mm) was used as a working electrode, a saturated calomel electrode (SCE) was used as a reference electrode, and a platinum wire was used as an auxiliary electrode. The modified electrode was placed in a Tris-HCl (0.1mol / L, pH=7.4) buffer containing 0.1mol / L ascorbic acid (AA) for Photocurrent Test, the test voltage is -0V.
[0068] AC impedance Experimental methods
[0069] AC impedance test is a test method that applies a small amplitude sinusoidal potential wave as a disturbance signal to the electrochemical system, and analyzes the charge transfer resistance on the electrode surface according to the radius of the arc in the Nyquist plot. The AC impedance experiment was carried out on a CHI 660E electrochemical workstation using a standard three-electrode system. The modified electrode was placed in a 5mmol / L [Fe(CN)6] 3- / 4- The test was carried out in a 1 mmol / L potassium chloride solution with a (1:1) ratio, a frequency range of 0.1 Hz to 100 kHz, and an applied amplitude of 5 mV.
[0070] Polyacrylamide gel electrophoresis experimental method
[0071] Polyacrylamide gel electrophoresis is a commonly used electrophoresis technique for separating oligonucleotides and proteins. Polyacrylamide gel electrophoresis experiments are used to verify the enzyme cleavage reaction in the solution and the probe binding reaction on the electrode. The specific operation steps are as follows:
[0072] ① Preparation of plastic sheet: Use Milli-Q to
[0073] After rinsing the comb, put it in the oven to dry, place the glue tank on the glue board, and put the comb aside for later use.
[0074] ② Gel preparation: Accurately pipette 7.5mL 40% Acr / Bis (19:1) gel preparation solution, 2mL 10×TBE buffer, 200μL 10% PAGE gel coagulant, 20μL PAGE gel accelerator and 10.28mL deionized water into a centrifuge tube, mix well and quickly add to the electrophoresis gel preparation mold, and try to avoid bubbles during the addition process. After complete solidification at room temperature, transfer to the electrophoresis tank, add a small amount of 1×TBE buffer to immerse the colloid, carefully remove the comb, and continue to add 1×TBE to the electrophoresis tank until half of the tank is located.
[0075] ③ Loading: Take 10 μL of sample and mix with 2 μL of 6× DNA loading buffer, then take 10 μL and add it to the polyacrylamide gel.
[0076] ④Electrophoresis: Turn on the power supply and react at 110V for 2h.
[0077] ⑤ Staining: Turn off the power, carefully take out the colloid, and place it in a liquid containing red fluorescent dye for staining for 30 minutes.
[0078] ⑥Imaging: Perform imaging analysis using a gel imaging analysis system.
[0079] Example 1Sc2O3@CuO
[0080] Synthesis method of Sc2O3@CuO: 0.3810g of scandium chloride hexahydrate, 0.6780g of copper nitrate trihydrate, and 0.1740g of 4-pyrazolecarboxylic acid were ultrasonically dissolved in 50mL of N,N′-dimethylformamide. After complete dissolution, the mixture was placed in a 100mL polytetrafluoroethylene autoclave, and the mixture was heated at 100°C for 16h to produce Figure 1 The metal organic framework MOF-919-Sc crystal shown on the left. After the solution is cooled to room temperature, centrifuged, washed with DMF several times, and placed in a 40°C oven to dry, a green powder is obtained. After grinding, it is transferred to a quartz crucible, placed in a muffle furnace, and heated to 550°C at 10°C / min for 1.5h to obtain a black powder, which is the Sc2O3@CuO polyhedron, such as Figure 1 As shown in the figure on the right.
[0081] from Figure 1 As can be seen in the left figure: MOF-919-Sc presents a nearly octahedral structure, with a single particle diameter of about 4μm; Figure 1 The right picture shows that the Sc2O3@CuO particles formed after MOF-919-Sc was calcined in an air atmosphere became smaller in size, with a diameter of about 2μm, and the morphology was wrinkled compared to the previous one, but the octahedral shape was still retained.
[0082] from Figure 2 The XRD spectrum shown shows that MOF-919-Sc does not show characteristic diffraction peaks, such as Figure 2 As shown in A; the calcined Sc2O3@CuO has obvious characteristic peaks. Figure 2B. The diffraction peaks at 2Theta of 22.0°, 31.5°, 36.4°, 43.0°, 52.4° and 62.5° correspond to the diffraction planes (211), (222), (400), (332), (433) and (622) of Sc2O3 (JCPDS No.43-1028). The diffraction peaks at 2Theta of 32.7°, 35.5°, 38.8°, 48.7°, 53.5°, 58.4° and 61.6° correspond to the diffraction planes (110), (-111), (111), (-202), (020), (202) and (-113) of CuO (JCPDS No.80-1914). Accompanied by the disappearance of the diffraction peak of MOF-919-Sc, it indicates that the bimetallic oxide precursor MOF-919-Sc is successfully converted into Sc2O3@CuO bimetallic oxide by calcination.
[0083] from Figure 3 The XPS spectrum of the Sc2O3@CuO polyhedron shown in the figure shows that the material synthesized by the method provided in this embodiment contains three elements: Cu, Sc and O. Figure 3 A. The Gaussian fitting method was used to fit and separate the O1s, Cu 2p and Sc 2p spectra. The results of the O 1s spectrum are shown in Figure 3 As shown in B, the O 1s spectrum can be decomposed into two peaks: the main peak at 529.5 eV and the shoulder peak at 531.5 eV, which belong to the lattice oxygen on the sample surface and the oxygen species adsorbed on the surface, respectively. Figure 3 As shown in C, the two diffraction peaks with binding energies of 933.6 eV and 953.6 eV correspond to Cu 2p 3 / 2 Orbitals and Cu 2p 1 / 2 orbital, which is similar to the Cu 2+ In addition, three satellite peaks of electronic oscillation appeared at 941.1eV, 943.6eV and 962.3eV, which were caused by the transfer of electrons from the ligand orbital to the 3d orbital of Cu, confirming that Cu 2+ It's 3D 9 The divalent form of the structure exists instead of Cu with filled d levels. + Cu 0 species, further proving the existence of CuO. The results of the Sc 2p spectrum fitting and peak separation are shown in Figure 3 D, where the asymmetric peak at 401.4 eV corresponds to the 2p 1 / 2 orbital, and 405.9 eV corresponds to the 2p 3 / 2The two peaks appearing at 413.1eV and 417.5eV may be attributed to the electron oscillation of Sc 2p orbital, which is caused by the complex multi-electron splitting, oscillation and uncertain overlapping binding energy that are unique to Sc as the first-row transition metal in the periodic table.
[0084] from Figure 4 The N2 adsorption-desorption isotherms and pore size distribution of the Sc2O3@CuO polyhedron shown in the figure show that the specific surface area of the Sc2O3@CuO polyhedron material is 55.28 m 2 / g, and the average pore size is 13.6nm. The larger pore size and high specific surface area exhibited by the material are conducive to the adsorption of light and give the material good photoelectric properties.
[0085] Example 2Sc2O3@CuO@AuNPs
[0086] The synthesis method of Sc2O3@CuO@AuNPs includes: taking 0.0030g of Sc2O3@CuO provided in Example 1 and dissolving it in 1mL Milli-Q water, ultrasonicating it until it is completely dispersed, adding 5mL of AuNPs solution, shaking it at a low speed for 14h in a dark environment, centrifuging it at 8000rpm / min, discarding the supernatant, and drying it to obtain Figure 5 The Sc2O3@CuO@AuNPs polyhedral material shown.
[0087] Figure 5 The high-resolution transmission electron microscopy (HRTEM) image shown in A shows that the Sc2O3@CuO@AuNPs polyhedron has obvious lattice fringes. The lattice with a lattice spacing of 0.404nm corresponds to the (211) crystal plane of Sc2O3, and the lattice fringes with a lattice spacing of 0.232nm correspond to the (111) crystal plane of CuO. Figure 5 The EDS element mapping shown in B reveals the element types and spatial distribution of the Sc2O3@CuO@AuNPs polyhedron. The analysis results show that O, Cu, Sc and Au elements exist in the prepared octahedron. The O, Cu, Sc elements clearly constitute the skeleton of the octahedron, while the Au element is scattered on the octahedron. This is because AuNPs are electrostatically adsorbed on the Sc2O3@CuO octahedron.
[0088] from Figure 6 From the UV-vis-NIR spectra of AuNPs and Sc2O3@CuO@AuNPs shown, it can be seen that the individual AuNPs show a characteristic absorption peak at 522nm, while the absorption peaks of Sc2O3@CuO@AuNPs are located at 522nm and 653nm, indicating the successful coupling of AuNPs; the absorption peak in the visible light region shows that Sc2O3@CuO@AuNPs have the potential to have excellent photoelectric properties.
[0089] Example 3 Photocurrent direction reversal mechanism
[0090] (1)Sc2O3@CuO / ITO
[0091] The preparation method of the Sc2O3@CuO / ITO electrode includes: adding the Sc2O3@CuO bimetallic oxide provided in Example 1 to 1 mL of 10 mmol / L Tris-HCl buffer to prepare a 1 mg / mL Sc2O3@CuO suspension for later use; applying 25 μL of the Sc2O3@CuO suspension to the surface of the ITO electrode, drying naturally, to obtain the Sc2O3@CuO / ITO electrode.
[0092] (2)Sc2O3@CuO / TiO2 / ITO
[0093] Preparation of TiO2 polyhedrons: NH2-MIL-125(Ti) was synthesized by solvothermal method. First, 0.5600g of aminoterephthalic acid was weighed and ultrasonically dissolved in a mixed solution of 1.5mL anhydrous methanol and 13.5mL DMF, followed by adding 0.6mL of tetraisopropyl titanate. After continued ultrasonic stirring, the mixture was transferred to a 100mL polytetrafluoroethylene autoclave and placed in an oven preheated to 150°C for 24h. After cooling to room temperature, the solid sample was centrifuged and washed with DMF and anhydrous methanol several times, and then transferred to a 40°C oven for drying to finally obtain NH2-MIL-125(Ti). NH2-MIL-125(Ti) was taken in a mortar, fully ground, and then transferred to a muffle furnace, heated to 350°C at 10°C / min for 4h to obtain a light yellow solid powder TiO2 polyhedron.
[0094] Preparation of TiO2 / ITO electrode: First, TiO2 was added into 1 mL 10 mmol / L Tris-HCl buffer to prepare a 1 mg / mL TiO2 suspension, and then 25 μL of the TiO2 suspension was added dropwise onto the surface of the ITO electrode and dried naturally to obtain a TiO2 / ITO electrode;
[0095] Preparation of Sc2O3@CuO / TiO2 / ITO electrode: 20 drops of 1 mg / mL Sc2O3@CuO suspension prepared in "(1) Sc2O3@CuO / ITO" of this example were added to the TiO2 / ITO electrode and dried naturally to obtain a Sc2O3@CuO / TiO2 / ITO electrode.
[0096] (3)Sc2O3@CuO@AuNPs / TiO2 / ITO
[0097] The TiO2 / ITO electrode was prepared by the same method as in “(2) Sc2O3@CuO / TiO2 / ITO” of this embodiment;
[0098] Preparation of Sc2O3@CuO@AuNPs / TiO2 / ITO electrode: first add the Sc2O3@CuO@AuNPs bimetallic composite material provided in Example 2 into 1 mL 10 mmol / L Tris-HCl buffer to prepare a Sc2O3@CuO@AuNPs suspension with a concentration of 1 mg / mL; then drop 20 μL of the Sc2O3@CuO@AuNPs suspension onto the surface of the TiO2 / ITO electrode and dry it naturally to obtain a Sc2O3@CuO@AuNPs / TiO2 / ITO electrode.
[0099] The structural properties of the TiO2 polyhedron prepared in this example are characterized as follows Figures 7-10 shown.
[0100] Figure 7 A shows the XRD spectrum of TiO2. It can be seen that the diffraction peaks of TiO2 dodecahedron are consistent with the results of the standard card (JCPDS-NO.99-0008). There are several higher diffraction peaks at 25.4°, 48.0°, 54.5°, and 62.5°, corresponding to the (101), (200), (211), and (213) crystal planes of TiO2, respectively, indicating that anatase phase TiO2 was successfully synthesized. Figure 7 Figure a in B is a HRTEM image of a TiO2 polyhedron. The lattice spacing of 0.356 nm corresponds to the (101) crystal plane of TiO2, which is consistent with the XRD results. Figure 7 Figures b, c, and d in A are the TEM images and EDS element mapping images of the TiO2 polyhedron, respectively. The results show that TiO2 retains its polyhedral structure and confirms the presence of Ti and O elements in the polyhedron. The above results indicate the successful preparation of TiO2 polyhedron.
[0101] from Figure 8 It can be seen from the XPS full spectrum shown in A that the two elements Ti and O exist in the above-mentioned light yellow solid powder material. Figure 8 The symmetrical peaks in the Ti 2p spectrum shown in B are at 458.7 eV and 464.3 eV, which can be attributed to the Ti 2p 3 / 2 and Ti 2p 1 / 2 , which is the Ti that forms TiO2 4+ peak. Figure 8 C is the O1s spectrum. It can be seen that two characteristic peaks appear at 529.9eV and 531.2eV, corresponding to O in the TiO2 lattice. 2-And the hydroxyl groups on the surface of the material. Thus, the XPS spectrum of TiO2 is basically consistent with the prior art.
[0102] from Fig. 9 The specific surface area of TiO2 polyhedron is calculated to be 60.95 m 2 / g. Fig. 9 The illustration is the pore size distribution curve, and the results show that the pore size of the prepared material is 4.78nm, which is a mesoporous structure.
[0103] Fig.10 The UV-vis-NIR absorption spectrum of TiO2 dodecahedron is shown. The maximum absorption band of TiO2 polyhedron is located at 420nm, the absorption band is red-shifted, and the visible light absorption is significantly enhanced. It has good photoelectric properties and is conducive to the construction of photocurrent (PEC) sensors.
[0104] Modified electrode performance verification
[0105] Photocurrent tests were carried out on the modified electrodes TiO2 / ITO, Sc2O3@CuO / ITO, Sc2O3@CuO / TiO2 / ITO and Sc2O3@CuO@AuNPs / TiO2 / ITO to investigate the photocurrent signals of each modified electrode. Fig.11 shown.
[0106] from Fig.11 It can be seen that the TiO2 / ITO electrode shows an anodic photocurrent signal of 3.02μA (curve a), and the Sc2O3@CuO / ITO electrode shows a cathode photocurrent signal of -2.45μA (curve b). When the Sc2O3@CuO polyhedron is modified on the surface of the TiO2 / ITO electrode, it is observed that the photocurrent direction generated by the Sc2O3@CuO / TiO2 / ITO modified electrode is opposite to that of the TiO2 / ITO photocurrent, and a large cathode photocurrent signal of -5.31μA appears (curve c), indicating that when the Sc2O3@CuO polyhedron is in direct contact with the TiO2 dodecahedron, the Sc2O3@CuO polyhedron can act as a signal reversal agent to achieve the reversal of the photocurrent direction of the TiO2 polyhedron. When AuNPs are adsorbed onto Sc2O3@CuO, the cathode photocurrent signal of the Sc2O3@CuO@AuNPs / TiO2 / ITO electrode is -9.26 μA, which is significantly larger than the photocurrent signal of the Sc2O3@CuO / TiO2 / ITO electrode. This is because the localized surface plasmon resonance (LSPR) effect of AuNPs significantly enhances the response value of the photocurrent signal.
[0107] Thus, the possible photocurrent direction reversal mechanism induced by Sc2O3@CuO@AuNPs on TiO2 is as follows: Fig.12 As shown. Under visible light irradiation, TiO2 polyhedron is excited, and photogenerated electrons / holes (photogenerated e - / h + ) are generated on their CB / VB respectively; then, the photogenerated - The CB transfer from the TiO2 polyhedron to the ITO electrode interface generates an obvious anodic photocurrent, such as Fig.12 As shown in the left picture. Fig.12 As shown in the right figure, after the Sc2O3@CuO@AuNPs heterojunction is loaded on the ITO / TiO2 electrode, TiO2, Sc2O3, CuO, and AuNPs are all excited under light, and photogenerated - / h + The photogenerated e on the CB / VB of TiO2, Sc2O3, and CuO - The electrons on the CuO CB are then transferred to the Sc2O3 CB and then to the CuO CB. Subsequently, the electrons on the CuO CB are consumed by the O2 in the buffer solution, while the AA in the solution reduces the generated holes. Since the energy level matching of TiO2, Sc2O3 and CuO can suppress the recombination of photogenerated electron / hole pairs, a significant cathode photocurrent can be observed. At the same time, the surface plasmon decay generates e inside the Au - / h + Hot electrons are then generated and escape from the Au nanostructure and are collected by contact with the electrode material; due to its strong LSPR effect, the hot electrons generated by Au nanostructures are injected into the CB of TiO2 and Sc2O3, and AuNPs, as plasma photosensitizers, enhance the photocurrent signal response value of the composite electrode.
[0108] Therefore, based on the excellent energy level matching between TiO2, Sc2O3, and CuO and the strong LSPR effect of AuNPs, Sc2O3@CuO@AuNPs can promote the separation and transfer of photogenerated electrons / holes in TiO2 polyhedrons, induce the reversal of the photocurrent direction of TiO2 polyhedrons, and form a TiO2 / / Sc2O3@CuO@AuNPs photocurrent direction reversal system.
[0109] Embodiment 4 Photocurrent direction reversal sensor
[0110] like Fig.13 As shown, this embodiment provides a method for preparing a photocurrent direction reversal sensor, comprising the steps of:
[0111] (1) Preparation of TiO2 / ITO electrode: The TiO2 / ITO electrode was prepared by the same method as "(2) Sc2O3@CuO / TiO2 / ITO" in Example 3;
[0112] (2) Adding crosslinking agent : Add 20 μL of 0.025 wt% CS aqueous solution dissolved in 1% acetic acid to the above TiO2 / ITO electrode and dry overnight; then drop 20 μL of 2.5% GLD solution and incubate at room temperature for 30 min to modify CS on the TiO2 / ITO electrode to obtain a CS / TiO2 / ITO electrode;
[0113] (3) Adding hairpin probe HP2 : HP2 was prepared into a 1 μmol / L solution using hybridization buffer, heated at 90°C for 5 min, and rapidly cooled to room temperature. Then 20 μL was added dropwise to the CS / TiO2 / ITO electrode and incubated at room temperature for 120 min, so that CS was used as a cross-linking agent to modify HP2 on the TiO2 / ITO electrode. Subsequently, 0.5 wt% BSA solution was added and placed at room temperature for 60 min to block unbound active sites, thereby obtaining a BSA / HP2 / CS / TiO2 / ITO electrode.
[0114] (4) Add auxiliary probe S2 , which step includes the following sub-steps:
[0115] 41) Magnetic bead washing: Take 100 μL of 2 mg / mL MNPs in a 2 mL low adsorption centrifuge tube, perform magnetic separation, and discard the supernatant; then add 100 μL of PBS buffer solution, mix thoroughly, perform magnetic separation, and discard the supernatant. Wash 3 times in total;
[0116] 42) Binding of MNPs to Apt: Add 100 μL of 2 μmoL / L Apt to the low adsorption centrifuge tube in step 41) above and mix thoroughly; shake the reaction at 37°C for 60 min, perform magnetic separation, discard the supernatant, add 100 μL of hybridization buffer and resuspend to obtain a MNPs-Apt resuspension;
[0117] 43) Hybridization of MNPs-Apt and S1: Take 100 μL of MNPs-Apt resuspension and 100 μL of 2 μmoL / L (excess) auxiliary probe S1 solution and mix thoroughly, place on a constant temperature oscillator at 37°C for 120 min to form magnetic nanoparticles-aptamer / auxiliary probe S1, magnetically separate, discard the supernatant, and wash repeatedly with hybridization buffer for 3 times, add 100 μL of hybridization buffer to resuspend, to form MNPs-Apt / auxiliary probe S1 resuspension, and store at 4°C for future use;
[0118] 44) Adding Kana standard solution: first prepare Kana into a standard solution with a concentration of 500 pmol / L, then add 100 μL of Kana standard solution of each concentration to the above-mentioned MNPs-Apt / auxiliary probe S1 resuspension, mix thoroughly, place on a constant temperature oscillator at 37°C for 90 min to allow MNPs-Apt / auxiliary probe S1 to release auxiliary probe S1 into the solution, and magnetically separate and obtain the supernatant, which contains the released auxiliary probe S1;
[0119] 45) Enzyme digestion reaction: 100 μL HP1 and 50 μL ExoⅢ enzyme were added to 100 μL supernatant containing the released auxiliary probe S1 obtained in step 44) above, mixed thoroughly, and placed on a constant temperature oscillator at 37°C for 120 min to release a large amount of single-stranded auxiliary probe S2 labeled with biotin;
[0120] 46) Inactivation of enzyme cleavage reaction: The solution after the reaction in step 45) is placed in a 90°C water bath for 10 minutes to inactivate the ExoⅢ enzyme and obtain an inactivated enzyme cleavage solution;
[0121] 47) Obtaining the S2 / BSA / HP2 / CS / TiO2 / ITO electrode: taking 20 μL of the solution after enzyme cleavage and inactivation, adding it dropwise to the surface of the BSA / HP2 / CS / TiO2 / ITO electrode, and incubating at 37° C. for 60 min to obtain the S2 / BSA / HP2 / CS / TiO2 / ITO electrode;
[0122] (5) Adding signal probe , which step includes the following sub-steps:
[0123] 51) Add 1 mL of 10 mmol / L Tris-HCl buffer to the Sc2O3@CuO@AuNPs provided in Example 2 to prepare a Sc2O3@CuO@AuNPs solution;
[0124] 52) Take 1 mL of Sc2O3@CuO@AuNPs solution, add 100 μL of 1 mg / mL SA solution, react at 4°C for 12 h; centrifuge and discard the supernatant, add 1 mL of 0.5 wt% BSA, react for 1 h, centrifuge again and discard the supernatant, add 1 mL of Tris-HCl and resuspend to prepare Sc2O3@CuO@AuNPs-SA suspension;
[0125] 53) Take 20 μL of Sc2O3@CuO@AuNPs-SA suspension and add it dropwise to the surface of S2 / BSA / HP2 / CS / TiO2 / ITO electrode and incubate at 37°C for 120 min to obtain Sc2O3@CuO@AuNPs-SA / S2 / BSA / HP2 / CS / TiO2 / ITO electrode, thereby completing the construction of the photoelectrochemical sensor.
[0126] The photoelectrochemical sensor constructed in this embodiment was used to perform the following three experiments: photocurrent experiment, AC impedance experiment and polyacrylamide gel electrophoresis experiment.
[0127] Photocurrent experiment: The photocurrent response of the modified electrode during the construction of the sensor was studied by photocurrent experiment. The results are as follows Fig.14 As shown. Fig.14 It can be seen that the TiO2 / ITO electrode shows an anode photocurrent of 3.02μA (curve a); with the gradual modification of CS, HP2, BSA and S2 on the electrode surface, the poorly conductive material on the electrode surface increases, resulting in a continuous weakening of the photocurrent response value (curve be, from 2.29μA to 1.65μA). However, when the modified electrode S2 / BSA / HP2 / CS / TiO2 / ITO is combined with the signal probe Sc2O3@CuO@AuNPs-SA through the biotin on HP2 and SA, the photocurrent response changes from the anode photocurrent (1.65μA) to the cathode photocurrent (-3.13μA). This is because the energy level matching between the TiO2 polyhedron and the Sc2O3@CuO@AuNPs polyhedron prompts the photogenerated electrons of the TiO2 polyhedron to transfer to the Sc2O3@CuO@AuNPs polyhedron, resulting in a reversal of the photocurrent direction. In this way, the successful construction of the photocurrent direction reversal sensor for detecting Kana provided by the bimetallic oxide in this embodiment is verified.
[0128] AC impedance experiment: The construction process of the biosensor provided in this embodiment was further analyzed by AC impedance experiment. The semicircle diameter of the electrochemical impedance spectrum reflects the interface R ct The value of Fig.15 As shown. Fig.15 It can be seen that for TiO2 / ITO electrode, R ct The value is 43.2Ω (curve a); due to the gradual assembly of CS, HP2, BSA and S2, the non-conductive substances on the electrode surface increase, R ct The value gradually increases (curve be, from 106.4Ω to 271.2Ω); when the modified electrode S2 / BSA / HP2 / CS / TiO2 / ITO is combined with the signal probe Sc2O3@CuO@AuNPs-SA, the impedance shows a slight change, and the value is 260.5Ω due to the weak conductivity of the semiconductor when it is not excited by visible light and the excellent conductivity of AuNPs. ct The changing trend of the values indicates that the photocurrent direction reversal sensor for detecting Kana was successfully constructed.
[0129] Polyacrylamide gel electrophoresis experiment: The feasibility of enzyme cleavage reaction in solution and probe binding reaction on electrode was verified by polyacrylamide gel electrophoresis experiment. Fig.16 As shown. Lane 1 is DNA Marker, and lanes 2 to 5 are Apt, S1, HP1, and HP2, respectively. All of them produce obvious bands. The position of the bands can be used as a reference to verify the subsequent reaction. Lane 6 is the reaction product of Apt and S1. An obvious band with a migration distance shorter than that of lanes 2 and 3 can be observed, proving the successful binding of Apt and S1. Lane 7 is the reaction product of Apt, S1, and Kana. The brightness and width of the band in this lane are slightly lower than those in lane 6, indicating that Apt and Kana specifically bind to each other, resulting in the release of part of S1. Lane 8 is the reaction product of Apt, S1, Kana, and HP1, and two obvious bands appear. The upper band is stronger than S1 and HP1, and the migration distance is shorter than HP1, indicating that S1 can open HP1; the lower band is in the same position as HP1, but the brightness and width are smaller than HP1, that is, HP1 that does not fully participate in the reaction. Lane 9 is the reaction product of Apt, S1, Kana, HP1 and ExoⅢ enzyme. The bands appearing from top to bottom are the double-stranded structure formed by S1 and HP1, HP1 not bound to S1, and the auxiliary probe S2 labeled with biotin produced after the enzyme cleavage reaction, indicating the successful progress of the enzyme cleavage reaction in the solution. Lane 10 is the product of the reaction of Apt, S1, Kana, HP1, ExoⅢ enzyme and HP2. The bands produced from top to bottom are the conjugate of S2 and HP2, HP2 and part of the Apt / S1 conjugate. The results of this lane verify that S2 produced after the enzyme cleavage reaction can open HP2 to bind to the electrode. The above results show the successful progress of the enzyme cleavage reaction in the solution and the reaction on the electrode.
[0130] Optimization experiment
[0131] There are two main factors that affect the photocurrent signal of the above-mentioned photocurrent direction reversal sensor provided by the embodiment of the present invention: one is the Kana reaction time in the sub-step of adding the Kana standard solution in the step (4) of adding the auxiliary probe S2, and the other is the signal probe incubation time in the sub-step (5) of adding the signal probe. The following is a further analysis and optimization experiment on these two factors.
[0132] Effect of Kana reaction time
[0133] Experimental conditions: other experimental conditions were kept unchanged, and 0, 30, 60, 90, and 120 min were selected as the reaction time between Kana and MNPs-Apt / auxiliary probe S1 in the above step "44) adding Kana standard solution". The other steps were referred to the corresponding steps of the above preparation method provided in this embodiment, so as to prepare the corresponding sensor. Each reaction time was measured in parallel 3 times, and the optimal reaction time was selected according to the size of the PEC signal value. The results are shown in FIG. Fig.17 shown.
[0134] Fig.17 Reflects the relationship between Kana's reaction time and photocurrent response. Fig.17 It can be seen that as the Kana reaction time gradually increases from 0 to 90 min, the photocurrent response generated by the modified electrode Sc2O3@CuO@AuNPs-SA / S2 / BSA / HP2 / CS / TiO2 / ITO also increases, but there is no obvious change in the photocurrent response value after 90 min. Therefore, 90 min was selected as the optimal Kana reaction time in subsequent experiments.
[0135] Effect of signal probe incubation time
[0136] Experimental conditions: above Step 53) Incubation of the signal probe The time was 0, 40, 80, 120, and 160 min respectively, and other experimental conditions were kept unchanged. The corresponding sensor was prepared according to the preparation method provided in this embodiment. Each reaction time was measured in parallel 3 times, and the optimal reaction time was selected according to the value of the photocurrent signal. The results are shown in FIG. Fig.18 shown.
[0137] from Fig.18 It can be seen that with the addition of the signal probe Sc2O3@CuO@AuNPs, the anode photocurrent first changes to the cathode photocurrent, and then the cathode photocurrent response value gradually increases with the extension of the binding time; after the binding time reaches 120 minutes, the cathode photocurrent response change trend gradually slows down. Therefore, 120 minutes was selected as the optimal binding time of the signal probe in subsequent experiments.
[0138] Therefore, the photocurrent direction reversal sensor prepared by the above method provided in this embodiment can be used for trace concentration detection of Kana.
[0139] Example 5 Application of Photocurrent Direction Reversal Sensor
[0140] (1) Standard curve
[0141] Experimental conditions: According to the preparation method provided in Example 4, photocurrent detection was performed on 0.1, 0.5, 1, 5, 10, 50, 100, and 500 pmol / L Kana standard solutions, respectively. Fig.19 As shown in A, three replicates were set for each concentration, and a linear fit was performed based on the experimental photocurrent response results to establish Fig.19 B shows the standard curve for detecting Kana.
[0142] from Fig.19 A It can be seen that as the concentration of Kana increases from 0.1pmol / L to 500pmol / L, the cathode photocurrent response value generated gradually increases. Fig.19B shows that in the range of Kana concentration from 0.1pmol / L to 500pmol / L, the cathode photocurrent response and the logarithm of Kana concentration show a good linear relationship, and the linear regression equation is:
[0143] y=-0.621x-1.502, y is I (μA), x is lgC Kana , R 2 =0.997.
[0144] (2) Detection limit
[0145] Prepare 10 sets of blank solutions, prepare sensors according to the preparation method provided in Example 4, and conduct photocurrent experiments. The average value of the photocurrent signals of the 10 sets of blank samples is I (μA) = 1.674, and the standard deviation SD of the 10 sets of blank samples is calculated to be 0.02. Substitute SD into the detection limit LOD, LOD formula: LOD = 3SD / |k| (k is the slope of the standard curve equation), and the LOD of this method is calculated to be 0.09pmol / L.
[0146] (3) Selectivity
[0147] Erythromycin ERY, doxycycline DOX, tetracycline TET, enrofloxacin ENR and streptomycin STR (which belong to the same aminoglycoside antibiotics as Kana and have very similar chemical structures) with similar structures were used as interfering substances. The established method was used to detect the mixed solutions of 500pmol / L ENR, 500pmol / L DOX, 500pmol / L TET, 500pmol / L ENR, 500pmol / L STR and 50pmol / L Kana, respectively. The photocurrent response values of each group of samples were compared. The results are shown in Figure 3. Fig. 20 shown.
[0148] Fig. 20 Display: When there is no target, the interference will not cause the photocurrent direction of the photocurrent sensor to flip, and the photocurrent response value generated by the interference is similar to that generated by the blank solution. In the presence of the target, the sensor shows a cathode photocurrent signal. The results for the mixed sample are the same as those when Kana exists alone. These phenomena show that this method has good selectivity.
[0149] (4) Stability
[0150] The photocurrent sensor prepared in Example 4 was stored in a 4°C refrigerator, and the PEC signal values after storage for 14 days and 21 days were measured, and the measured values were compared with the photocurrent response values corresponding to the initial target. The results are as follows: Fig.21The Kana concentration selected for the determination was 50 pmol / L.
[0151] from Fig.21 It can be seen that the photoelectric response value of the photocurrent sensor can maintain 97.6% of the initial measured value (-2.56μA) at 14 days and 96.8% of the initial measured value at 21 days, which shows that the sensor has good stability.
[0152] (5) Reproducibility
[0153] Under the same experimental conditions, five parallel tests were performed on the 5 pmol / L Kana standard solution according to the method provided in Example 4. Five PEC sensors were constructed and the corresponding photocurrent response values were detected. The results are shown in FIG. Fig. 22 shown.
[0154] Fig. 22 The results show that the RSD of the photocurrent response values of 5 parallel tests is 1.2%, which shows that the detection method constructed in the embodiment of the present invention has good reproducibility.
[0155] (6) Spike recovery rate
[0156] The sample for spiked recovery determination was prepared with PBS as solvent. Kana standard solutions were prepared into three concentrations (1, 10, 100 pmol / L) of low, medium and high concentrations, respectively, and detected using the established method. The measured PEC signal value was substituted into the standard curve to obtain the measured concentration, and the spiked recovery of the method was calculated according to the formula: Spiked recovery rate = (measured value / added value) × 100%, and the results are shown in Table 2. It can be seen from Table 2 that the biosensor constructed in the embodiment of the present invention meets the requirements for detecting kana in actual samples.
[0157] Table 2: Kana spike recovery (n=3)
[0158] Addition amount (pmol / L) Actual measurement (pmol / L) RSD(%) Recovery rate (%) 1 0.96±0.03 3.1 96.6 10 9.48±0.78 8.2 94.8 100 100.53±6.85 6.8 100.5
[0159] (7) Actual sample testing
[0160] 1) Sample pretreatment
[0161] Milk and honey are complex matrix samples and require certain pretreatment to reduce interference. The sample processing method is as follows:
[0162] ① Milk sample: Accurately measure 1 mL of milk, add 10 mL of pH=6.0 PBS buffer and 1 mL of 10% trichloroacetic acid solution, vortex mix and ultrasonicate for 20 min. Centrifuge the mixed solution at 8000 r / min for 5 min, aspirate the supernatant, adjust the pH to neutral with NaOH solution, filter through a 0.22 μm filter membrane, and store at 4°C.
[0163] ②Honey sample: weigh 0.5 g honey into a 50 mL centrifuge tube, add 1 mL of pH 6.0 PBS buffer solution and shake to mix, then add 6 mL of Milli-Q water, vortex extract for 10 min, centrifuge at 8000 r / min for 5 min, aspirate the supernatant, filter through a 0.22 μm filter membrane, and store at 4°C.
[0164] 2) Sample determination
[0165] The treated milk and honey samples were added with a certain concentration of Kana standard solution to form spiked samples, and the photocurrent sensor provided in Example 4 of the present invention was used for detection. The detection results are shown in Table 3.
[0166] ① The actual sample determination step of the photocurrent direction reversal sensing method: the spiked samples of milk and honey were diluted into three concentrations of low, medium and high (5, 50, 500 pmol / L), and the detection was performed respectively according to the method steps provided in Example 4 of the present invention, and each sample was paralleled 3 times. The measured photocurrent signal value was substituted into the standard curve to calculate the content of Kana in the milk and honey solutions, and then the spiked recovery rate at each concentration was calculated.
[0167] ② ELISA Kit test actual sample steps: Dilute the spiked samples of milk and honey into three concentrations within the linear range of ELISA: low, medium, and high (0.6, 1.2, and 4 ng / mL), and test them according to the steps in the ELISA manual. Each sample is tested in triplicate. Substitute the obtained values into the ELISA standard curve to calculate the content of Kana in the solution, and then calculate the spiked recovery rate at each concentration.
[0168] 3) ELISA Kit Operation Steps
[0169] ① Set up standard wells and sample wells, and add 50 μL of standard of different concentrations to each standard well.
[0170] ② First add 10μL of the sample to be tested to the sample well, and then add 40μL of sample diluent; do not add to the blank well.
[0171] ③Except for the blank wells, add 100 μL of detection antibody labeled with horseradish peroxidase (HRP) to each well of the standard well and sample well, seal the reaction wells with a sealing film, and incubate in a 37°C constant temperature box for 60 min.
[0172] ④Discard the liquid and pat dry on absorbent paper. Then fill each well with washing solution, let it stand for 1 minute, shake off the washing solution, pat dry on absorbent paper, and repeat this washing process 5 times.
[0173] ⑤ Add 50 μL of substrate A and B to each well and incubate at 37°C in the dark for 15 min.
[0174] ⑥ Add 50 μL of stop solution to each well and measure the OD value of each well at a wavelength of 450 nm within 15 minutes. Substitute the obtained value into the standard curve to calculate the concentration of Kana in the solution.
[0175] Table 3 Spiked recovery of Kana concentration in actual samples (n=3)
[0176]
[0177] Note: Due to the high sensitivity of the PEC method, the added value determined by the PEC method is the value of the sample determined by the ELISA method after appropriate dilution.
[0178] It can be seen from Table 3 that the spiked recovery rate of milk samples detected by the photocurrent direction reversal sensing method provided by the embodiment of the present invention is between 92.6% and 102.3%, and the spiked recovery rate of honey samples is between 96.5% and 104.5%. The ELISA Kit measured the spiked recovery rates of three concentrations (0.6, 1.2, and 4 ng / mL) of actual samples at low, medium, and high concentrations. The recovery rates of milk samples were between 99.2% and 103.3%, and the recovery rates of honey samples were between 99.2% and 105.5%, respectively. Comparison of the spiked recovery results of the two methods has a good correlation, indicating that the photocurrent direction reversal sensing method provided by the embodiment of the present invention has a certain reliability in detecting the Kana concentration in actual samples and can be used to monitor the Kana content in milk or honey.
[0179] Therefore, the photoelectrochemical biosensor provided in the embodiment of the present invention is based on MOFs-derived TiO2 nanomaterials, combined with the photocurrent direction reversal strategy and enzyme cleavage signal amplification technology, to establish a new photocurrent direction reversal sensor for detecting Kana. The constructed sensor has the advantages of high sensitivity, good accuracy, strong selectivity, high stability, good reproducibility, etc., and can achieve rapid detection of antibiotics in milk and honey samples, which has potential value in ensuring food safety.
[0180] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A bimetallic oxide, characterized in that: The invention discloses Sc2O3@CuO, an octahedral crystal structure composed of Sc2O3 and CuO. The bimetallic oxide is obtained by heating a metal organic framework MOF-919-Sc crystal at 350-650°C, wherein the metal organic framework MOF-919-Sc crystal is ultrasonically dissolved in 50 mL N,N′-dimethylformamide by 0.3810 g of scandium chloride hexahydrate, 0.6780 g of copper nitrate trihydrate and 0.1740 g of 4-pyrazolecarboxylic acid. After being completely dissolved, the mixture is placed in a 100 mL polytetrafluoroethylene autoclave and heated at 100°C for 16 h to obtain the obtained product.
2. A method for preparing the bimetallic oxide as claimed in claim 1, comprising: The metal organic framework MOF-919-Sc crystals were heated at 350-650°C to obtain black powder, namely Sc2O3@CuO. The preparation method of the metal organic framework MOF-919-Sc crystal includes: taking 0.3810 g of scandium chloride hexahydrate, 0.6780 g of copper nitrate trihydrate and 0.1740 g of 4-pyrazolecarboxylic acid, ultrasonically dissolving them in 50 mL of N,N′-dimethylformamide, placing them in a 100 mL polytetrafluoroethylene autoclave after they are completely dissolved, and heating the mixture at 100 °C for 16 h.
3. A bimetallic oxide composite material, characterized in that: A composite material Sc2O3@CuO@AuNPs mainly composed of the bimetallic oxide according to claim 1 and nano-gold particles electrostatically adsorbed on the surface of the bimetallic oxide octahedron.
4. A photoelectric current signal inversion type photoelectrochemical sensor, characterized in that: It comprises a TiO2 / ITO electrode and a hairpin probe HP2 labeled with an amino group, an auxiliary probe S2 labeled with biotin and a signal probe respectively modified on the surface of the TiO2 / ITO electrode, wherein the signal probe is Sc2O3@CuO@AuNPs coated with streptavidin, and the Sc2O3@CuO@AuNPs is the composite material according to claim 3; The auxiliary probe S2 is mainly obtained by the enzymatic cleavage reaction between the auxiliary probe S1 released by competition and the hairpin probe HP1 labeled with biotin under the action of an enzyme, wherein the auxiliary probe S1 released by competition is mainly obtained by mixed incubation of magnetic nanoparticles-aptamer / auxiliary probe S1 and the antibiotic to be tested; The auxiliary probe S2 opens the hairpin probe HP2, exposing the biotin on the auxiliary probe S2 on the surface of the TiO2 / ITO electrode. The biotin binds to the streptavidin, so that the signal probe is modified to the surface of the TiO2 / ITO electrode to form a Sc2O3@CuO@AuNPs / TiO2 / ITO electrode whose photoelectric signal is opposite to that of the TiO2 / ITO electrode.
5. A method for preparing the photoelectrochemical sensor according to claim 4, comprising the steps of: Adding a crosslinking agent: first adding a chitosan solution to the surface of the TiO2 / ITO electrode, then dropping a glutaraldehyde solution and incubating at room temperature, sequentially modifying the TiO2 / ITO electrode with chitosan and glutaraldehyde to obtain a CS / TiO2 / ITO electrode; wherein, The TiO2 / ITO electrode can generate an initial anode photocurrent signal; Adding hairpin probe HP2: first assembling the hairpin probe HP2 onto the CS / TiO2 / ITO electrode by incubation at room temperature, and then blocking the active sites on TiO2 with bovine serum to prepare a BSA / HP2 / CS / TiO2 / ITO electrode; Adding auxiliary probe S2: first react and combine carboxyl magnetic beads with aptamers to obtain MNPs-Apt; then hybridize MNPs-Apt with auxiliary probe S1 to form MNPs-Apt / S1, and obtain MNPs-Apt / S1 resuspension; add the antibiotic to be tested to the MNPs-Apt / S1 resuspension for reaction, release the auxiliary probe S1 in the MNPs-Apt / S1, magnetically separate, and take the supernatant containing the auxiliary probe S1; add the hairpin probe HP1 labeled with biotin and ExoⅢ enzyme to the supernatant containing the auxiliary probe S1 for enzyme cleavage reaction to form the auxiliary probe S2 labeled with biotin; assemble the auxiliary probe S2 onto the BSA / HP2 / CS / TiO2 / ITO electrode to obtain the S2 / BSA / HP2 / CS / TiO2 / ITO electrode; Adding a signal probe: first react the composite material described in claim 4 with streptavidin to synthesize Sc2O3@CuO@AuNPs-SA, and prepare a Sc2O3@CuO@AuNPs-SA suspension; add the Sc2O3@CuO@AuNPs-SA suspension to the surface of the S2 / BSA / HP2 / CS / TiO2 / ITO electrode for incubation to obtain a Sc2O3@CuO@AuNPs-SA / S2 / BSA / HP2 / CS / TiO2 / ITO electrode with a reversed photocurrent signal.
6. The preparation method according to claim 5, characterized in that: The antibiotic is Kana, tetracycline, oxytetracycline or penicillin.
7. Use of the photoelectric chemical sensor according to claim 4 or 5 in detecting the concentration of antibiotics in food.
8. The use according to claim 7, characterized in that The method comprises the following steps: placing the photoelectrochemical sensor in a Tril-HCl buffer solution containing 0.1 M ascorbic acid at pH 7.4 to perform photocurrent detection, and detecting the photocurrent signal of the antibiotic at different concentrations; and constructing a linear equation between the antibiotic concentration and the photocurrent signal according to the detection result.
9. The use according to claim 8, characterized in that In the step of adding the auxiliary probe S2, the antibiotic solution to be tested is added to the MNPs-Apt / S1 resuspension, and after being evenly mixed, the mixture is placed on a constant temperature oscillator at 37° C. for reaction for 30 to 120 min, and the auxiliary probe S1 in the MNPs-Apt / S1 is released through competition, and then the supernatant is obtained by magnetic separation, and the supernatant contains the released auxiliary probe S1; In the step of adding the signal probe, the Sc2O3@CuO@AuNPs-SA suspension is added to the surface of the S2 / BSA / HP2 / CS / TiO2 / ITO electrode and incubated at 37°C for 40 to 160 min to obtain a Sc2O3@CuO@AuNPs-SA / S2 / BSA / HP2 / CS / TiO2 / ITO electrode.
10. The use according to claim 9, characterized in that: When the concentration of antibiotic Kana ranges from 0.1 to 500 pmol / L, the constructed linear regression equation is y=-0.621x-1.502, where x is lgC Kana , R 2 =0.997, the detection limit is 0.09 pmol / L; wherein y is the photocurrent signal detected by the sensor, in μA; C Kana Represents the concentration of Kana.